Social Care Character Education On Farming Family - Fitri Andika, Muhammad Fauzi; Indriastuti, Ana; Mayang, Lintang; Handoyo, Eko; Wijayanti, Tutik (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2024)
This study aims to explain the form of social care character and the strategy of instilling social care character in farmer families. This research is qualitative research that uses a descriptive method based on a farmer's family in Demangan Village, Karangdowo Kabupaten Klaten District. The subject of the study was a peasant family. Data collection uses observation, interview, and documentation techniques. This research is based on the theory of Pierre Bourdieu who initiated his thoughts on habitus, arena, and capital that emphasized structure in shaping social life. The results showed that the form of social care character in the family includes empathy for others, sympathy, carrying out social actions, helpfulness, altruism, givers, having initiative, being willing to sacrifice, not prioritizing profits, prioritizing usefulness for others, and being sincere. The strategy of instilling character values in farming families uses strategies of exemplary, habitual, reinforcement or advice, environmental conditioning, and local wisdom. The form of social care character and the strategy of instilling a social care character takes place in the family environment, school environment, and community environment